Properties of Linear Induction Drive of Actuating Systems - Poska, A.; Rinkeviciene, R.; Savickiene, Z. (Elektronika ir Elektrotechnika, 1998)
Article deals with small power low speed linear induction drives of actuating systems. It is proved that current of these linear induction motors (LIM) does not depend on slip, transients of current are short and dynamical amplitudes are small. There are presented expressions, allowing to calculate the steady state and dynamic characteristics when the drive is controlled by changing supply voltage frequency.